Genetic testing in benign familial epilepsies of the first year of life: Clinical and diagnostic significance. Issue 3 (29th January 2013) - Zara, Federico; Specchio, Nicola; Striano, Pasquale; Robbiano, Angela; Gennaro, Elena; Paravidino, Roberta; Vanni, Nicola; Beccaria, Francesca; Capovilla, Giuseppe; Bianchi, Amedeo; Caffi, Lorella; Cardilli, Viviana; et al.
Summary Purpose To dissect the genetics of benign familial epilepsies of the first year of life and to assess the extent of the genetic overlap between benign familial neonatal seizures (BFNS), benign familial neonatal‐infantile seizures (BFNIS), and benign familial infantile seizures (BFIS). Methods Families with at least two first‐degree relatives affected by focal seizures starting within the first year of life and normal development before seizure onset were included. Families were classified as BFNS when all family members experienced neonatal seizures, BFNIS when the onset of seizures in family members was between 1 and 4 months of age or showed both neonatal and infantile seizures, and BFIS when the onset of seizures was after 4 months of age in all family members. SCN2A, KCNQ2, KCNQ3, PPRT2 point mutations were analyzed by direct sequencing of amplified genomic DNA. Genomic deletions involving KCNQ2 and KCNQ3 were analyzed by multiple‐dependent probe amplification method. Key Findings A total of 46 families including 165 affected members were collected. Eight families were classified as BFNS, 9 as BFNIS, and 29 as BFIS. Genetic analysis led to the identification of 41 mutations, 14 affecting KCNQ2, 1 affecting KCNQ3, 5 affecting SCN2A, and 21 affecting PRRT2. The detection rate of mutations in the entire cohort was 89%. In BFNS, mutations specifically involve KCNQ2. In BFNIS two genes are involved (KCNQ2, six families; SCN2A, two families). BFIS families are the most genetically heterogeneous, with all four genes involved, although about 70% of them carry a PRRT2 mutation. Significance Our data highlight the important role of KCNQ2 in the entire spectrum of disorders, although progressively decreasing as the age of onset advances. The occurrence of afebrile seizures during follow‐up is associated with KCNQ2 mutations and may represent a predictive factor. In addition, we showed that KCNQ3 mutations might be also involved in families with infantile seizures. Taken together our data indicate an important role of K‐channel genes beyond the typical neonatal epilepsies. The identification of a novel SCN2A mutation in a family with infantile seizures with onset between 6 and 8 months provides further confirmation that this gene is not specifically associated with BFNIS and is also involved in families with a delayed age of onset. Our data indicate that PRRT2 mutations are clustered in families with BFIS. Paroxysmal kinesigenic dyskinesia emerges as a distinctive feature of PRRT2 families, although uncommon in our series. We showed that the age of onset of seizures is significantly correlated with underlying genetics, as about 90% of the typical BFNS families are linked to KCNQ2 compared to only 3% of the BFIS families, for which PRRT2 represents the major gene.